Reframing Proxemics in the Perspective of Collectivism Societies (Study of Residents of Riverbank Relocation in Vertical Settlements in Jakarta) - Tobing, Melati Mediana (International Journal of Social and Management Studies, 2022)
Mutual cooperation is used by most Asians for living in their challenging environment. On the riverbanks of Ciliwung in Jakarta, the Kampung Pulo’s people work together facing the floods that inundated their roof for days, and feel comfortable living in this area until the rest of their lives. But this area becomes a disaster for the city and should be revitalized. While developing a metropolitan city, the city planner uses vertical occupancy as a solution to relocate residents from slums. There is a change in the meaning of space and distance and the relations between citizens in this settlement. The elevator, closing doors, none of the terraces to sit in front of their house, are destructive to this collectivistic person on interacting and sharing information. Citizens must be adapted to these modern residential boxes, which are more efficient and economical, and common use for the individualistic society. This article was written based on research about how these residents in Jakarta use space and distance for communicating in their new vertical space, through the method of interviewing and observing. The informant was born in Kampung Pulo and living in rental housing belongs to the city government in Jatinegara Barat, East of Jakarta. There are some findings of distinctive values that differ significantly from individualistic culture as basic research of the proxemic theory, that could be considered in the construction of vertical housing for collectivist communities.